A Discussion on the Notion of Unutilized Spaces: The Case of Maraş in Cyprus - Işçioğlu, Deniz (TURKIYE ORTADOGU AMME IDARES IENSTITUSU, 2024)
The notion of ‘’space’’ has been associated with different meanings during different times in the course of history, sometimes representing an abstract structure, standing, some other time, for a concrete one. A piece of space can have a sense only in association with human beings. Several explanations have been put forward to explain the notion of space, but what this paper aims to discuss is how we should construct, or how the construct should be of, the notional framework of unutilized spaces where people do not live in, those they have abandoned or have been forced to abandon. This study attempts to redefine the notion of space in association with spaces people no more use for the purposes of residence or production. During this time, the war-torn pieces of land and premises located in the buffer zone turned into, and still are, unutilized spaces, standing lifeless in ruins where no human activity is performed. These spaces, sometimes a village or a church or a foundation in some cases, are usually controversial spaces in respect of property rights. The area of Maraş that has remained unutilized to-date on the grounds of political reasons can be given as an example of such a space. The study results have also revealed that the interviewers had different images about Maraş. In conclusion, a new need for conceptualization other than the ones available in the literature has arisen. Thus the study has introduced, out of this need, the notion of ‘’Imaginational Space’’, based on the imagination of spaces “that may be used again one day”. The subject of space can be reproduced, and continue to live on, in the minds of people as “Imaginational spaces” also without the control of the triad of human-state-capital. © 2024 TURKIYE ORTADOGU AMME IDARES IENSTITUSU. All rights reserved.
Kullanılmayan Mekânlar Üzerine Bir Kavram Tartışması: Kıbrıs Maraş Bölgesi Örneği
Keywords: Imaginational Space; Maraş; North Cyprus; Space